Real-time fluorescence and colorimetric identification of bulbus fritillariae using recombinase assisted loop-mediated isothermal DNA amplification (RALA) - Wei, Yinghua; Ding, Sheng; Chen, Gangyi; Dong, Juan; Du, Feng; Huang, Xin; Cui, Xin; Chen, Rong; Tang, Zhuo (Frontiers in Plant Science, 2022)
Bulbus Fritillariae (BF) is a kind of herbal medicine widely used in many countries including China, Japan, Korea and so on. Among the known BF medicinal materials, Bulbus Fritillariae cirrhosae (BF cirrhosae) was reported to have the best curative effect. Due to the limited resources of BF cirrhosae, a lot of adulterants have emerged in the market, impairing the market order, resource development, and above all, clinical efficacy. Here, a novel nucleic acid amplification technique, Recombinase Assisted Loop-mediated isothermal DNA Amplification (RALA), was used to establish a real-time flurescence isothermal molecular authentication method for five commonly used BF drugs. Moreover, this RALA-based assay can also be developed as a colorimetric detection method for on-site detection （shown in the graphic abstract）. Both real-time fluorescence and visual methods could detect as low as 0.1% genuine targets in the mixed samples. In summary, here we report an isothermal detection system for five kinds of BF available in the market, providing a new choice for the molecular identification of BF drugs and showing promise in the laboratory testing as well as field identification of other medicinal herbs.